2011
DOI: 10.4103/0971-6580.84260
|View full text |Cite
|
Sign up to set email alerts
|

Chronic fluoride toxicity and myocardial damage: Antioxidant offered protection in second generation rats

Abstract: This experiment was designed to investigate the extent of peroxidative changes and histological alterations in the myocardium of rats exposed to high fluoride for two generations, in addition to ameliorative role of selenium and vitamin E on the above indices. Adult albino Wistar rats were given fluoride through drinking water (200 ppm F) and maintained subsequently for two generations, while they were exposed to fluoride throughout the experiment. Fluoride treatment significantly increased the lipid peroxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 13 publications
3
11
0
Order By: Relevance
“…TNF-␣ acts as a major mediator in the pathogenesis of cardiac injury, promoting inflammation, apoptosis and accumulation of extracellular matrix. Several studies have shown the higher levels of inflammatory cytokines, such as TNF-␣, IL-1␤, and IL-6 are involved in processes leading to cardiac remodelling such as hypertrophy, fibrosis, and apoptosis [61]. In our study, we found that TNF-␣-level was increased from the heart tissue of F intoxicated rats clearly indicates the cardiac inflammation, which coincides with the reports of Nabavi et al [9] in F intoxicated rats.…”
Section: Discussionsupporting
confidence: 92%
“…TNF-␣ acts as a major mediator in the pathogenesis of cardiac injury, promoting inflammation, apoptosis and accumulation of extracellular matrix. Several studies have shown the higher levels of inflammatory cytokines, such as TNF-␣, IL-1␤, and IL-6 are involved in processes leading to cardiac remodelling such as hypertrophy, fibrosis, and apoptosis [61]. In our study, we found that TNF-␣-level was increased from the heart tissue of F intoxicated rats clearly indicates the cardiac inflammation, which coincides with the reports of Nabavi et al [9] in F intoxicated rats.…”
Section: Discussionsupporting
confidence: 92%
“…However, more and more evidence showed that fluoride intoxication produces oxidative stress and damages various tissues [25][26][27][28]. The cardiovascular systems are susceptible to a high concentration of fluoride, because many cardiovascular dysfunctions have been observed, such as the decreasing of cardiac output, the occurrence of arrhythmias, and heart block [7,8,29]. However, the mechanisms of fluorosis in the cardiovascular system need to be further illustrated.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorine is an active nonmetallic element, which easily interacts with calcium and magnesium in the blood, thus causing blood calcium metabolism disorder, leading to the functional and organic damage to the cardiovascular and other systems [6]. Studies showed that fluoride has severe detrimental effects on cardiac function in atherosclerosisrelated myocardial injury and pathophysiological remodeling [7][8][9][10][11]. However, very few studies have ever addressed the mechanism of action of fluorosis in cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%
“…It is also known to cause damage to major organs of the body including the heart and the gastrointestinal tract. Its accumulation in soft tissues causes injury by reducing the potential of scavenging free radicals production, which critically injures the biological membranes [5]. It also intensifies free radical production and a disturbed antioxidant level leads to oxidative stress, which is known to be a key etiopathological factor in a variety of cardiac diseases [6,7].…”
Section: Methodsmentioning
confidence: 99%